(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Companies activities do not always satisfy customers’ demands. The question is to find circumstances which influence customer satisfaction. It can have an objective and subjective nature. Customers show appreciation through increasing their demand, loyalty to company products, brand etc. Companies and their customers establish relationships based on trust, which companies should support and develop. Scientific literature has shown a huge variety of characteristics and indicators which companies used to satisfy customers. Such methods give to the scientists and companies many combinations to design and implement them in a different companies circumstances. The paper shows that satisfaction is an adjustable indicator, it should determine by combinations of internal variables of customer behavior. That explains the fact that indexes of appreciation should be personal for every customer and cover a process of buying and usage service or a product. Moreover, customer satisfaction provokes other changes and influences investors and competitor’s behavior. The article identifies factors influencing customer satisfaction on the three levels of such a process: before the buying, during and after the transaction. The buyer’s satisfaction justly depends on the characteristics related to the quality of the product, and the very process of buying, emotions that follow this process. On the overload market, the importance of psychological factors of consumer satisfaction increases. They can be divided into factors related to the product or service or to the customer and the seller personality. Such order can be a basis for future models of consumer satisfaction.